EFFECT OF BREAST SELF-EXAMINATION EDUCATION ON ADOLESCENTS’ KNOWLEDGE AND MOTIVATION - Melan Veoleta Sijabat; Kamariyah Kamariyah; Yuliana Yuliana; Yulia Indah Permata Sari; Meinarisa Meinarisa (Jurnal Multidisipliner Kapalamada, 2026)
Breast cancer is a major global and national health problem, including among adolescents. Early detection through Breast Self-Examination (BSE/SADARI) is recommended to improve early diagnosis and prevention. This study aimed to analyze the effect of BSE education on knowledge and motivation among female students at SMP Negeri 11 Jambi City. A quantitative pre-experimental design with a one-group pretest–posttest approach was used. The sample consisted of 40 students selected using stratified sampling. Data were collected using validated and reliable questionnaires and analyzed using the Wilcoxon Signed Rank Test. The results showed a significant increase in knowledge (p = 0.000) and motivation (p = 0.000) after BSE education. The findings indicate that BSE education effectively improves students’ knowledge and motivation, supporting early breast cancer awareness among adolescents.